2014
DOI: 10.1890/13-1821.1
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural practices indirectly influence plant productivity and ecosystem services through effects on soil biota

Abstract: Abstract. It is well established that agricultural practices alter the composition and diversity of soil microbial communities. However, the impact of changing soil microbial communities on the functioning of the agroecosystems is still poorly understood. Earlier work showed that soil tillage drastically altered microbial community composition. Here we tested, using an experimental grassland (Lolium, Trifolium, Plantago) as a model system, whether soil microbial communities from conventionally tilled (CT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 83 publications
3
67
1
5
Order By: Relevance
“…Tillage represents a disturbance of the soil habitat and can mechanically disrupt filamentous organisms, decrease soil structure, temporarily increase organic matter decomposition, and alter water and nutrient content and distribution [143,144]. Tillage-induced disturbance often has a negative impact on soil biota and the services that they supply [144][145][146]. Tillage most noticeably impacts large soil biota like earthworms [144] and filamentous organisms like fungi, particularly AM fungi [147].…”
Section: A General Approach: Modify the Whole Soil Communitymentioning
confidence: 99%
“…Tillage represents a disturbance of the soil habitat and can mechanically disrupt filamentous organisms, decrease soil structure, temporarily increase organic matter decomposition, and alter water and nutrient content and distribution [143,144]. Tillage-induced disturbance often has a negative impact on soil biota and the services that they supply [144][145][146]. Tillage most noticeably impacts large soil biota like earthworms [144] and filamentous organisms like fungi, particularly AM fungi [147].…”
Section: A General Approach: Modify the Whole Soil Communitymentioning
confidence: 99%
“…Surface dwelling earthworms and soil microarthropodes are negatively influenced in number and species diversity by mechanical soil cultivation, especially ploughing (Crittenden et al 2015;Ernst and Emmerling 2009;Peigné et al 2009). Tests in other countries have shown that ploughing reduces the biodiversity of arbuscular mycorrhiza in the soil (Köhl et al 2014;Säle et al 2015), and the fields in rotation are generally ploughed more in organic than in conventional agriculture. However, research has shown that the diversity of microorganisms is higher in soils with organic compared to conventional production (Oehl et al 2004;Stagnari et al 2014), so other factors may have greater influence on the soil biodiversity than ploughing.…”
Section: Influence On Nature and Biodiversitymentioning
confidence: 99%
“…Soil disturbances can disrupt the existing mycorrhizal network that connects mycorrhizae and plants together (Sheng et al, 2012;Kohl et al, 2014). Once disturbed, the AMF network will take a long time to restore back to its original state.…”
Section: Introductionmentioning
confidence: 99%